Building the hospital event-based surveillance system in Viet Nam: a qualitative study to identify potential facilitators and barriers for event reporting - Hien Do; Hien T Ho; Phu D Tran; Dang B Nguyen; Satoko Otsu; Cindy Chiu de Vázquez; Tan Q Dang; Quang D Tran; Van Anh Pham; Nanako Mikami; Masaya Kato (World Health Organization Regional Office for the Western Pacific, 2020)
Introduction: Hospitals are a key source of information for the early identification of emerging disease outbreaks and acute public health events for risk assessment, decision-making, and public health response. The objectives of this study were to identify potential facilitators and barriers for reporting of unusual events from the curative sector to the preventive medicine system in Viet Nam. Methods: In 2016, we conducted 18 semi-structured in-depth interviews and 9 focus group discussions with representatives from the curative and preventive medicine sectors in four provinces. We transcribed the interviews and focus group discussions and conducted a thematic analysis of the factors that appeared to affect public health event reporting. Results: We identified five major themes. Firstly, the lack of a legal framework to guide reporting meant there was an over-reliance on internal procedures. Secondly, participants reported the importance of an enabling environment to facilitate reporting such as leadership support and having focal points for reporting. Thirdly, potential benefits for reporting were seen such as support during outbreaks and receiving feedback. Fourthly, some challenges prohibited timely reporting such as not perceiving reporting to be the task of the curative sector and hesitancy to report without laboratory confirmation. Finally, the limited resources and specialist capacities in remote areas hindered timely detection and reporting of unusual events. Discussion: This study identified potential opportunities to promote the detection and reporting of unusual events from health care workers to the public health sector, and thus improving the overall health security system in Viet Nam and beyond.